2004
DOI: 10.1289/ehp.7024
|View full text |Cite
|
Sign up to set email alerts
|

Lead, Diabetes, Hypertension, and Renal Function: The Normative Aging Study

Abstract: In this prospective study, we examined changes in renal function during 6 years of follow-up in relation to baseline lead levels, diabetes, and hypertension among 448 middle-age and elderly men, a subsample of the Normative Aging Study. Lead levels were generally low at baseline, with mean blood lead, patella lead, and tibia lead values of 6.5 μg/dL, 32.4 μg/g, and 21.5 μg/g, respectively. Six percent and 26% of subjects had diabetes and hypertension at baseline, respectively. In multivariate-adjusted regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 24 publications
7
112
0
3
Order By: Relevance
“…Second, exposure to lead and cadmium has been related to a higher risk of several pathologic conditions that are also linked to frailty. Environmental exposure to lead in the elderly has been associated with cognitive decline (Bandeen-Roche et al 2009;Grashow et al 2013;Nordberg et al 2000;Power et al 2014;Shih et al 2006;van Wijngaarden et al 2011), impaired motor skills (Grashow et al 2013), increased blood pressure (Perlstein et al 2007), ischemic heart disease (Jain et al 2007), decreased renal function (Tsaih et al 2004), falls and fractures in women (Khalil et al 2008), hearing loss (Park et al 2010) and vision problems (Schaumberg et al 2004;Wu et al 2014). Cadmium, for which fewer studies have been conducted in the elderly, has also been associated with an increased risk of atherosclerotic plaques (Fagerberg et al 2012), peripheral artery disease (Tellez-Plaza et al 2013a), osteoporosis (Engstrom et al 2011;Gallagher et al 2008) and macular degeneration (Shiue 2013;Wu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, exposure to lead and cadmium has been related to a higher risk of several pathologic conditions that are also linked to frailty. Environmental exposure to lead in the elderly has been associated with cognitive decline (Bandeen-Roche et al 2009;Grashow et al 2013;Nordberg et al 2000;Power et al 2014;Shih et al 2006;van Wijngaarden et al 2011), impaired motor skills (Grashow et al 2013), increased blood pressure (Perlstein et al 2007), ischemic heart disease (Jain et al 2007), decreased renal function (Tsaih et al 2004), falls and fractures in women (Khalil et al 2008), hearing loss (Park et al 2010) and vision problems (Schaumberg et al 2004;Wu et al 2014). Cadmium, for which fewer studies have been conducted in the elderly, has also been associated with an increased risk of atherosclerotic plaques (Fagerberg et al 2012), peripheral artery disease (Tellez-Plaza et al 2013a), osteoporosis (Engstrom et al 2011;Gallagher et al 2008) and macular degeneration (Shiue 2013;Wu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, sBPb levels as low as 5-9 mg/dl has been associated with an increased risk of death from all causes, cardiovascular disease, and cancer (Menke et al, 2006;Schober et al, 2006). Others have suggested that patients with metabolic syndrome may have a greater susceptibility for toxicity at lower blood and organ Pb levels (Tsaih et al, 2004;Park et al, 2006). Since metabolic syndrome is a criterion for weight loss surgery, a lower threshold of ''normal'' blood Pb levels may be relevant to this population.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Pb poisoning in diabetic subjects have been recognised [25]. Epidemiologic studies in animals have reported Pb toxic effects at high levels of exposure may contribute to the progression of diabetes complications in dia-betic patients [26].…”
Section: Introductionmentioning
confidence: 99%